Wie alt ist der Kapitän wirklich? Über die Bewährung der Mathematik an der Realität oder Wittgenstein, Regeln und der Mathematikunterricht (mathematica didactica, 2002)
In the paper I discuss the way in which mathematics education is supported by „reality“. According to Wittgenstein mathematics has to correspond to our acting in a sense that essentially differs from a mere occupation with application-orientated exercises.